Beyond Cars: Fischer‐Tropsch Synthesis for Non‐Automotive Applications. Issue 5 (8th February 2019) - Sun, Jian; Yang, Guohui; Peng, Xiaobo; Kang, Jincan; Wu, Jinhu; Liu, Guangbo; Tsubaki, Noritatsu
Abstract: As a century‐old classical reaction, Fischer‐Tropsch (F‐T) synthesis is undergoing new developments especially in its applications of producing jet fuel, olefins, aromatics and oxygenated chemicals, which are completely different from the conventional F‐T product, gasoline, diesel and wax. Producing above new products is not obeying famous ASF distribution law, requiring revolutionary design of new F‐T catalysts and reaction pathways. A mass of new research directions on F‐T synthesis for these liquid fuels and high‐value chemicals are successfully proposed. This review spotlights recent new advances based on F‐T synthesis for non‐automotive applications, and discusses its new possible directions in future. Abstract : Going beyond cars : This Minireview spotlights recent new advances based on Fischer‐Tropsch synthesis for non‐automotive applications, such as jet fuel, olefins, aromatics and oxygenated chemicals, which are completely different from the conventional Fischer‐Tropsch product, and discusses its new possible directions in future.